Development of Engineered Cementitious Composites Using Sea Sand and Metakaolin - Yao, Qiyao; Li, Zuo; Lu, Chenyu; Peng, Linxin; Luo, Yuejing; Teng, Xiaodan (Frontiers in Materials, 2021)
This study investigates the possibility of using sea sand instead of silica sand in producing engineered cementitious composites (ECC), the optimal mix proportion, mechanical behavior and the erosive effect of chloride ion on sea sand ECC (SECC). Nine groups of SECC specimens were prepared based on orthogonal test design, cured for uniaxial tensile, uniaxial compression and fracture energy tests. Roundness and sphericity of sea sand and silica sand were quantified by digital microscopy. The microstructure and composition of SECC were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The mix proportions of SECC with tensile strain capacity of more than 2% and compressive strength of more than 60 MPa obtained. The factor analysis of these serial tests showed that both the contents of fly ash and sea sand have significant effect on the compressive strength and tensile strain capacity of SECC. Fracture energy test showed that the matrix fracture toughness of SECC increases significantly with increasing sea sand content. The XRD analysis showed that the addition of metakaolin can enhance the ability of SECC to bind chloride ions, and with the increase of chloride ion content, this ability of SECC to bind chloride ion will be improved. The results of this study provide further evidence of the feasibility of using sea sand in the production of ECC to meet the requirements of diverse concrete components on ductility and durability.